Review of Compilation of Islamic Law Against Interfaith Marriage Prohibition results in the registration of marriages - Nur Fika Palilati (Estudiante Law Journal, 2022)
This research aims to review the compilation of Islamic law on the prohibition of interfaith marriages, which will result in marriage registration. The research method is judicial sociological research, which employs a descriptive qualitative research approach and interactive analysis techniques. The results of this study indicate that the prohibition on interfaith marriages does result in the registration of marriages, with Muslims registering marriages through the office of religious affairs. Interfaith marriages are prohibited in the rules of the Compilation of Islamic Law, one of which is explained in Article 40 KHI. Wherever it is mentioned in the article, women and men are prohibited from marrying women and men of other religions. The KUA can register Muslim marriages, while the Civil Registry Office can only register marriages for people who are married to a religion other than Islam. This means that a marriage can only be registered at the Population Service, or KUA, if it has been legalized by law or a recognized religion.